Impression cytologic analysis after corneal cross-linking and insertion of corneal ring segments for keratoconus: two-year results - Renesto, Adimara da Candelaria [UNIFESP] (2012)
PURPOSE: To report the impression cytologic results after corneal cross-linking and insertion of intrastromal corneal ring segments for keratoconus. METHODS: Thirty-nine eyes were distributed into two groups: 1) cross-linking group (patients underwent corneal cross-linking procedure), and 2) riboflavin eyedrops group (patients received 0.1% riboflavin (w/v) eyedrops in 20% dextran solution for 1 month). After 3 months, all patients underwent insertion of intrastromal corneal ring segments. Impression cytologic specimens were obtained from all eyes at baseline, at 1 month and 3 months after cross-linking or riboflavin eyedrops, and again at 6 months, 1 year, and 2 years after intrastromal corneal ring segment insertion. RESULTS: Patients in the cross-linking group demonstrated improvement in the cell-to-cell contact of epithelial cells and the nucleus-to-cytoplasm ratio on the temporal conjunctiva after treatment (P=0.008 and P=0.047), respectively. On the superior conjunctiva, increases in goblet cell density (P=0.037) and level of organization of nuclear chromatin (P=0.010) after treatment were noted. Patients in the riboflavin eyedrops group demonstrated improvement in the cell-to-cell contact of epithelial cells on the superior conjunctiva after treatment (P=0.021). On the temporal conjunctiva, an improvement in the cell-to-cell contact of epithelial cells (P<0.001) and increases in the nucleus-to-cytoplasm ratio (P<0.001), goblet cell density (P=0.001), and less keratinization (P=0.011) were noted. No changes were identified on the cornea for either group. Fisher's exact test comparison of the impression cytologic total scores after treatment revealed no difference between groups. CONCLUSION: Despite changes in some conjunctival parameters (e.g., cell-to-cell contact of epithelial cells, nucleus-to-cytoplasm ratio, level of organization of nuclear chromatin, goblet cell density, and keratinization), comparison of the total impression cytologic scores revealed no difference between groups.